Penilaian Kinerja Bank Mega Syariah Dengan Metode Balanced Scorecard Periode 2015-2019 - Aminatun, Wahyuni; Parno, Parno; Pratiwi, Angrum (Institut Agama Islam Negeri Ponorogo, 2021)
The purpose of this study was to determine the performance assessment of Bank Mega Syariah with the Balanced Scorecard method. There are four aspects of assessment in the balanced scorecard, namely financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. The research method used is descriptive quantitative. The type of data is secondary, sourced from the Financial Statements and Annual Reports that have been published by Bank Mega Syariah. The data collection technique uses the documentation method from the official website of the Financial Services Authority, and the official website of Bank Mega Syariah. Data analysis technique is to calculate the score of each perspective, based on predetermined criteria. The results obtained from the analysis of the performance assessment of Bank Mega Syariah using the Balanced Scorecard method for the 2015-2019 period, for a financial perspective the NPF ratio shows a healthy predicate, the FDR ratio with a fairly healthy predicate, and an ROA ratio with a healthy predicate. healthy predicate, ROE ratio with fairly healthy predicate, BOPO ratio with very healthy predicate, and CAR ratio with very healthy predicate. For the customer perspective, it shows a decrease in Market Share and shows an increase in Customer Profitability. For the internal business process perspective, it shows an increase in Process Innovation and an increase in After Sales Service. For the learning and growth perspective, it shows a decrease in employee retention and shows an increase in employee productivity.Tujuan penelitian ini adalah mengetahui penilaian kinerja Bank Mega Syariah dengan metode Balanced Scorecard. Terdapat empat aspek penilaian dalam balanced scorecard, yaitu perspektif keuangan, perspektif pelanggan, perspektif proses bisnis internal, dan perspektif pembelajaran dan pertumbuhan. Metode penelitian yang digunakan adalah kuantitatif deskriptif. Jenis data yaitu sekunder, yang bersumber dari Laporan Keuangan dan Laporan Tahunan yang telah dipublikasi oleh Bank Mega Syariah. Teknik pengumpulan data menggunakan metode dokumentasi dari website resmi Otoritas Jasa Keuangan, dan website resmi Bank Mega Syariah. Teknik analisis data yaitu dengan menghitung skor masing-masing perspektif, berdasarkan kriteria yang telah ditetapkan. Hasil yang diperoleh dari kajian analisis penilaian kinerja Bank Mega Syariah dengan menggunakan metode Balanced Scorecard periode 2015-2019, untuk perspektif keuangan pada rasio NPF menunjukkan predikat sehat, rasio FDR dengan predikat cukup sehat, rasio ROA dengan predikat sehat. predikat sehat, rasio ROE dengan predikat cukup sehat, rasio BOPO dengan predikat sangat sehat, dan rasio CAR dengan predikat sangat sehat. Untuk perspektif pelanggan menunjukkan penurunan Pangsa Pasar dan menunjukkan peningkatan Profitabilitas Pelanggan. Untuk perspektif proses bisnis internal menunjukkan peningkatan dalam Inovasi Proses dan peningkatan Layanan Purna Jual. Untuk perspektif pembelajaran dan pertumbuhan menunjukkan penurunan Retensi Karyawan dan menunjukkan peningkatan Produktivitas Karyawan.